Media Regulation in Nigeria’s Digital Age: A Systematic Review of Policy Frameworks - Inobemhe, Kelvin; Ossai, Collins Oyemike (Academia Journal of Humanities & Social Sciences, 2026)
This study was conducted to examine media regulations in the digital era in Nigeria, focusing on their implications for free expression. The research was motivated by the increasing attempts by the Nigerian government to regulate digital platforms, particularly social media, through controversial bills such as the “Protection from Internet Falsehood and Manipulation Bill 2019” and the “National Commission for the Prohibition of Hate Speech Bill.” These legislative efforts have sparked widespread concerns about the potential infringement on citizens’ rights to free speech. The general objective of the study was to explore existing literature to ascertain the balance between digital media regulation and the protection of fundamental rights in Nigeria’s evolving digital landscape. The study is based on a systematic literature review, relying on secondary data sources, including journal articles, online resources, and reports. The findings revealed a significant tension between the government’s desire to regulate harmful content and the risk of suppressing free expression. It was revealed that vague and broad provisions in the proposed legislation could be exploited to target critics and stifle dissent. The study concludes that while there is a need for regulation to address misinformation and hate speech, such measures must be transparent, participatory, and aligned with the global best practices to prevent the erosion of democratic principles. The key recommendation for Nigeria is to develop a balanced regulatory framework that protects both public order and the right to free expression.